2011
DOI: 10.1152/ajpcell.00501.2010
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled estrogen receptor 1-mediated effects in the rat myometrium

Abstract: G protein-coupled estrogen receptor 1 (GPER), also named GPR30, has been previously identified in the female reproductive system. In this study, GPER expression was found in the female rat myometrium by reverse transcriptase-polymerase chain reaction and immunocytochemistry. Using GPER-selective ligands, we assessed the effects of the GPER activation on resting membrane potential and cytosolic Ca(2+) concentration ([Ca(2+)](i)) in rat myometrial cells, as well as on contractility of rat uterine strips. G-1, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
2
31
0
1
Order By: Relevance
“…Extracellular administration of LPI resulted in a relatively slow response that reached a peak within 1-2 min and continued with a plateau phase, whereas LPI microinjection induced a fast and transitory effect similar to that reported upon activation of other intracellular GPCRs, such as those for angiotensin II (29,33,62) or endothelin 1 (28). We have noticed likewise discrepancies in the plasmalemmal-initiated versus intracellularly initiated Ca 2ϩ responses by the G protein-coupled estrogen receptor GPER/GPR30 (34,63), which is reportedly expressed at both sites (64,65). LPI is a lipid messenger, expected to get partitioned in the lipid bilayer and reach the other side of the sarcolemma.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Extracellular administration of LPI resulted in a relatively slow response that reached a peak within 1-2 min and continued with a plateau phase, whereas LPI microinjection induced a fast and transitory effect similar to that reported upon activation of other intracellular GPCRs, such as those for angiotensin II (29,33,62) or endothelin 1 (28). We have noticed likewise discrepancies in the plasmalemmal-initiated versus intracellularly initiated Ca 2ϩ responses by the G protein-coupled estrogen receptor GPER/GPR30 (34,63), which is reportedly expressed at both sites (64,65). LPI is a lipid messenger, expected to get partitioned in the lipid bilayer and reach the other side of the sarcolemma.…”
Section: Discussionsupporting
confidence: 71%
“…Measurement of Membrane Potential-The relative changes in membrane potential of single cardiomyocytes were evaluated using bis-(1,3-dibutylbarbituric acid) trimethine oxonol, bis-(1,3-dibutylbarbituric acid) trimethine oxonol, a slow-response, voltage-sensitive dye, as described previously (32)(33)(34). Upon membrane hyperpolarization, the dye concentrates in the cell membrane, leading to a decrease in fluorescence intensity, whereas depolarization induces the sequestration of the dye into the cytosol, resulting in an increase of the fluorescence intensity (35).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these results suggest that the majority of E2's reproductive functions are mediated by ERa and that GPER and G-1 lack the classic feminizing effects of ERa and E2. Nevertheless, G-1 has been demonstrated to increase the frequency and amplitude of rat myometrial contractions (Tica et al, 2011), as well as the oxytocininduced contractile response of human myometrium explants (Maiti et al, 2011), suggesting limited specific functions of GPER in the uterus. A role for GPER in mammalian primordial follicle formation has been reported (Wang et al, 2008b), and in nonmammalian vertebrates, G-1 has also been shown to reduce both spontaneous and progestin-induced oocyte maturation, suggesting a role for GPER in maintaining oocyte meiotic arrest (Pang et al, 2008;Peyton and Thomas, 2011).…”
Section: A Reproductionmentioning
confidence: 98%
“…In addition to these pathways, GPER has also been demonstrated to mediate Gα s protein activation (Thomas et al, 2005) leading to adenylyl cyclase activation and cAMP accumulation (Filardo et al, 2002), which further leads to PKA activation (Zucchetti et al, 2013) and transcriptional activation of CREB (Kanda and Watanabe, 2004) as well as vascular effects (Lindsey et al, 2013b) among other sequellae. Additional downstream pathways reported to be activated by GPER include PI3K (Revankar et al, 2005; Petrie et al, 2013), PKC (Goswami et al, 2011), calcium mobilization (Revankar et al, 2005; Tica et al, 2011), and other ion channels (Fraser et al, 2010; Goswami et al, 2011). Interestingly, many studies have observed that a vast majority of GPER is expressed in intracellular membranes (Revankar et al, 2005; Otto et al, 2008; Filardo and Thomas, 2012), with little expressed at the cell surface in most cells and cell lines likely due to both inefficient export mechanisms, which involve receptor activity-modifying protein 3 (RAMP3) (Bouschet et al, 2012; Lenhart et al, 2013), as well as constitutive GPER internalization (Cheng et al, 2011a; Cheng et al, 2011b).…”
Section: Gper Ligands and Signaling Mechanismsmentioning
confidence: 99%